2015
DOI: 10.1063/1.4914943
|View full text |Cite
|
Sign up to set email alerts
|

Sub-nA spatially resolved conductivity profiling of surface and interface defects in ceria films

Abstract: Spatial variability of conductivity in ceria is explored using scanning probe microscopy with galvanostatic control. Ionically blocking electrodes are used to probe the conductivity under opposite polarities to reveal possible differences in the defect structure across a thin film of CeO2. Data suggest the existence of a large spatial inhomogeneity that could give rise to constant phase elements during standard electrochemical characterization, potentially affecting the overall conductivity of films on the mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…Polarization of CGnano.-Both the negative and the positive polarization experiments were completely reversible and did not lead to a detectable change in the surface topography. This is consistent with previous studies by Farrow et al, 27 who reported irreversible surface damage only for polarization of ceria films with currents higher than 1 nA. As the bias was kept between +5 and -5 V, the currents were below this threshold in our study.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Polarization of CGnano.-Both the negative and the positive polarization experiments were completely reversible and did not lead to a detectable change in the surface topography. This is consistent with previous studies by Farrow et al, 27 who reported irreversible surface damage only for polarization of ceria films with currents higher than 1 nA. As the bias was kept between +5 and -5 V, the currents were below this threshold in our study.…”
Section: Resultssupporting
confidence: 94%
“…The authors were able to show locally resolved evidence for the existence of space charge regions at ceria grain boundaries and at the sample surface. 27 Yang et al used a similar setup to study the effect of adsorbed water on the surface of ceria thin films during polarization with high applied biases in the range of several volts 28,29 and Kumar et al demonstrated that this technique could also be used to monitor the local oxygen reduction (or evolution) on Pt-decorated YSZ 30 or to detect the change of electrochemical processes on Sm-doped ceria thin films during polarization with high biases under variation of temperature. 31 The effects on the surface potential introduced by changing the steady state of an acceptor doped ceria system by polarization were at first explained by an ionization process leading to the local oxidation of Ce 3+ to Ce 4+ .…”
mentioning
confidence: 99%
“…This is in good accordance to the initial idea, that the local defect mobility is directly influenced by polarization with sufficiently high voltages due to ionization of defect associates. A similar difference for cathodic and anodic polarization has been reported by Farrow et al during assessment of the local spatial distribution of conductance on CeO2 thin films [32].…”
Section: Discussionsupporting
confidence: 83%
“…Similar effects have already been shown for polarization with oxygen conductive perovskites using electrochemical strain microscopy [37]. In contrast to these measurements, the polarization experiments presented here did not lead to a detectable change in the surface topography, which is consistent to experiments by Farrow et al [32], who reported irreversible surface damage for polarization of ceria films with currents higher than 1 nA.…”
Section: Kpfm Measurements After Polarizationsupporting
confidence: 92%
See 1 more Smart Citation